2006
DOI: 10.1021/ac061134j
|View full text |Cite
|
Sign up to set email alerts
|

DNA Detection on Plastic:  Surface Activation Protocol To Convert Polycarbonate Substrates to Biochip Platforms

Abstract: A mild and efficient surface activation protocol to convert polycarbonate (PC) substrates, e.g., plastic bases of compact disks, to biochip platforms for DNA probe immobilization and target detection is described. The preparation procedure (activation, patterning, and coupling) is simple and effective; the on-chip hybridization is sensitive and selective. Particularly, UV/ozone treatment of PC sheets produces a hydrophilic surface with a high density of reactive carboxylic acid groups [(4.8 +/- 0.2) x 10-10 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
98
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 47 publications
4
98
0
Order By: Relevance
“…High background fluorescence on plastic supports is often due to nonspecific adsorption of the labeled target onto the substrate (4,13,19). In the present study, we report high signal-to-background ratios.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…High background fluorescence on plastic supports is often due to nonspecific adsorption of the labeled target onto the substrate (4,13,19). In the present study, we report high signal-to-background ratios.…”
Section: Discussionsupporting
confidence: 56%
“…However, the high autofluorescence of standard polymeric materials is not compatible with a highly sensitive detection method that employs fluorescent targets. Plastic microarray hybridizations compatible with fluorescent dyes have been developed previously (5,6,13). However, these investigators reported only hybridizations with labeled oligonucleotides, and the specific hybridization signal-to-background ratios were relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 However, contact angle increases on polymer surfaces over time aer the treatment (hydrophobic recovery effect) due to the exibility and reorganization of the bonds within the polymer chains. [36][37][38] Here, we report a facile method for the generation of very stable superhydrophilic/superhydrophobic patterned surfaces. Superhydrophobic surfaces were prepared from nanostructured ormosil nanoparticles synthesized via sol-gel method where hydrophobic surface chemistry and high surface roughness were combined in one-pot approach.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy is based on hydrophobic interactions between probes and polycarbonate, showing high immobilization yields. 186 Following this research line, Li et al 187 developed bioassays performed directly on a CD in a line array format. The aim was to detect different types of biochemical recognition reactions (biotin-streptavidin binding, DNA hybridization and protein-protein interactions) with standard optical drives.…”
mentioning
confidence: 99%